1992
DOI: 10.1073/pnas.89.23.11603
|View full text |Cite
|
Sign up to set email alerts
|

Purification of human leukotriene C4 synthase.

Abstract: Leukotriene (LT) C4 synthase, the enzyme that catalyzes the conjugation ofLTA4 with reduced glutathione to form LTC4, was purified to homogeneity from the KG-1 myeloid cell line after solubilization of the microsomes utilizing a combination of 0.4% sodium deoxycholate and 0.4% Triton X-102. The solubilized enzyme was then applied to an S-hexylglutathione-agarose column that was eluted by the use of7.5 mM probenecid. After removal of the probenecid by sequential concentration and dilution in an Amicon concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 27 publications
(27 reference statements)
0
41
0
1
Order By: Relevance
“…Incubation of LTA, with mastocytoma membrane vesicles in the presence of glutathione resulted in the formation of LTC, (unpublished results), indicating the presence of LTC, synthase as another potential LTC,-binding protein in our membrane preparation. LTC, synthase was found to be a unique membrane-bound enzyme distinct from other cytosolic and microsomal glutathione S-transferases [36,37,[46][47][48]. Recent studies in dimethylsulfoxide-differentiated U 937 cells indicated that human LTC, synthase is composed of an 18-kDa protein that is enzymically active as a homodimer and contains a phosphorylation site [36,37,491.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of LTA, with mastocytoma membrane vesicles in the presence of glutathione resulted in the formation of LTC, (unpublished results), indicating the presence of LTC, synthase as another potential LTC,-binding protein in our membrane preparation. LTC, synthase was found to be a unique membrane-bound enzyme distinct from other cytosolic and microsomal glutathione S-transferases [36,37,[46][47][48]. Recent studies in dimethylsulfoxide-differentiated U 937 cells indicated that human LTC, synthase is composed of an 18-kDa protein that is enzymically active as a homodimer and contains a phosphorylation site [36,37,491.…”
Section: Discussionmentioning
confidence: 99%
“…LTC 4 is formed by conjugation of LTA 4 with the tripeptide glutathione through the catalysis of LTC 4 synthase. Stimulated by divalent cations and phosphatidylcholine, LTC 4 synthase is an 18-kDa protein with a wide tissue distribution (31,32). After LTC 4 synthesis, the multidrug transporter ATP-binding cassette (Abc)c1 (formerly known as MRP-1) actively transports LTC 4 out of the cell, where LTD 4 and LTE 4 are formed through the elimination of glutamine and glycine, respectively, by ␥-glutamyl transpeptidase and dipeptidase (33)(34)(35).…”
Section: Leukotrienesmentioning
confidence: 99%
“…FLAP may serve as an arachidonic acidbinding protein, allowing arachidonic acid to be presented to 5-LO for conversion to both 5-HPETE and LTA 4 (14)(15)(16)(17)(18). To form LTC 4 , LTA 4 is conjugated with reduced glutathione by LTC 4 synthase, a 17-kDa integral membrane protein that shares a high identity with FLAP (19)(20)(21)(22)(23). Two untested models for the membrane organization of LTC 4 synthesis can be proposed.…”
mentioning
confidence: 99%